OUTDOOR ACTIVITIES TO PROMOTE CREATIVE THINKING IN PRESCHOOL CHILDREN - Krauksta, Daina; Rozenvalde, Paula; Ciekurs, Kalvis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article analyzes the influence of outdoor activities to creative thinking in children of preschool age (5-6 years). In today's education already from pre-school age is not sufficient with traditional learning. At the same time the use of this knowledge must be developed for use in various life situations. This requires creative thinking - the creation of new ideas. Perschoolers imagination knows no boundaries and therefore must be used. Excellent confirmation gives the outdoor environment - nature and natural processes, changing weather conditions.Outdoor physical activities is a precondition for the acquisition of skills necessary for life, while creative thinking promotes the development of these skills in the further use of the various life-changing situations. The study analyzes the outdoor activities lesson content and their organization, and proven creative thinking of fostering positive trends in the experimental group compared to the children in the control group.